Using THELI pipeline in order to reduce Abell 226 multi-band optical images - Joveini, R.; Sotoudeh, S.; Roozrokh, A.; Taheri, M. (Advances in Astronomy and Space Physics, 2013)
In this paper we review THELI (Erben & Schrimer, 2005), an image processing pipeline developed to reduce multipointing optical images taken by mosaic CCD cameras. This pipeline works on raw images by removing several instrumental contaminations, implementing photometric calibration and astrometric alignment, and constructing a
deep co-added mosaic image complemented by a weight map. We demonstrate the procedure of reducing NGC 3923 images from raw data to the final results. We also demonstrate the quality of our data reduction strategy using mag-count and mag-error in mag plots. Emphasis is mainly placed on photometric calibration which is of great interest to us due to our scientific case. Based on the cross-association of the extracted catalogue against a reference catalogue of stellar magnitudes, zero-point calibration is performed. Our data reduction strategy and the method employed for cross-correlating large catalogues is also presented.